Pengaruh Kualitas Pelayanan dan Promosi terhadap Kepuasan Pelanggan di Sun Bread Batam - Marpaung, Gustina; purba, Daris (LPPM Universitas Putera Batam, 2022)
This research aims to studying whether there was an influence of service quality and promotion in customer satisfaction at New Sun Bread KDA located in Batam. This research uses a causal associative research and uses quantitative mothod. The data is collected by distributing questionnaires to respondents written by the researcher in the questionnaire forms. Sampling uses the incidental method and rate only reached 5% so that a sample of 186 respondents could be taken. The data analysis in this study uses multiple linear regression analysis. So the results obtained from this study indicates that the service quality variable affects customer satisfaction, and this is also proven by the results of the the test which also shows > t table, while the promotion variable has no effect on customer satisfaction. and also this can be justified because in the previous test where account < ttable and the results are significant. The result of this study can be concluded that there is a positive and significant effect between the X1 variable on the Y variable, while for X2 there is no influence on the Y but there is a significant influence between the two variables, namely X simultaneously on the Y variable. Keywords: Customer Satisfaction; Promotion; Service Quality.